The Effect of Transformational Leadership Style on Innovation Behaviour among Bank Employees in South Africa during COVID-19 - Nyamunda, Takudzwa Joshua; Bezuidenhoud, Leon; Walt, Ruan Van Der (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
The turn of the century has brought its challenges for South African banks which include but are not limited to increasing competition and rising costs as a result of increasing regulatory requirements, financial and technological innovation, entry of large foreign banks in the retail banking environment, and challenges of the recent financial crisis (Mabwe & Webb, 2010). Furthermore, with respect to current economic challenges Buehler et al. (2020) predict that banking institutions will have to play a critical role post-Covid-19 in stabilizing the system for their customers, employees, and economies. The crisis inturn also presents a chance to continue to build the economy in the post-Covid-19 environment and an opportunity for African organisations to become hubs for innovation (Tyson, 2020). The aim of this study was to assess the relative effect of Transformational Leadership on Innovation Behaviour in a group of bank employees and determine if there are any significant differences in innovation behaviour on the basis of age. The primary hypothesis that transformational leadership will have an effect on Innovation behavior was confirmed, while the secondary hypothesis which relates to the difference in Innovation Behaviour on the basis of age was not confirmed. Innovation Behaviour is considered to be a valuable and necessary skill in the current global and regional economic climate. Recommendations are put forward on how Transformational leadership can be utilized in banking institutions to increase employee Innovation Behaviour. Recommendations include inter-alia the need for banking institutions to look at leader behaviours in terms areas for development and the investment into creating a culture that encourages learning. The analysis was based on data from a survey sent to 813 South African bank employees with 80 respondents who completed an online questionnaire. Pearson-Product Moment Correlation and Regression statistics were used to answer the primary hypothesis, while the Kruskal-Wallis test was utilized to examine how age affects the differences in innovation behavior.